Séneca en los Andes. Neoestoicismo y crítica social en Quito a fines del siglo XVII - Ponce Leiva, Pilar (Pontificia Universidad Católica del Perú. Fondo Editorial, 2007)
This article analyzes the influence of neo-stoicism in the works of Francisco Rodríguez Fernández, who was one of the most outstanding readers of Seneca in Quito toward the end of the seventeenth century. The article highlights how he used this line of thought as an ethical and political instrument to combatcorruption and injustices in Quito’s society, and to contribute to the regeneration of the Spanish monarchy and its American possessions.
Keywords: Historia; https://purl.org/pe-repo/ocde/ford#6.01.01